Endogenous hydrogen sulfide contributes to uterine quiescence during pregnancy. Issue 5 (May 2017) - You, Xingji; Chen, Zixi; Zhao, Huina; Xu, Chen; Liu, Weina; Sun, Qianqian; He, Ping; Gu, Hang; Ni, Xin
Abstract : Recent evidence suggests that uterine activation for labor is associated with inflammation within uterine tissues. Hydrogen sulfide (H2 S) plays a critical role in inflammatory responses in various tissues. Our previous study has shown that human myometrium produces H2 S via its generating enzymes cystathionine-γ-lyase (CSE) and cystathionine-β-synthetase (CBS) during pregnancy. We therefore explored whether H2 S plays a role in the maintenance of uterine quiescence during pregnancy. Human myometrial biopsies were obtained from pregnant women at term. Uterine smooth muscle cells (UMSCs) isolated from myometrial tissues were treated with various reagents including H2 S. The protein expression of CSE, CBS and contraction-associated proteins (CAPs) including connexin 43, oxytocin receptor and prostaglandin F2α receptor determined by Western blot. The levels of cytokines were measured by ELISA. The results showed that CSE and CBS expression inversely correlated to the levels of CAPs and activated NF-κB in pregnant myometrial tissues. H2 S inhibited the expression of CAPs, NF-κB activation and the production of interleukin (IL)-1β, IL-6 and tumor necrosis factor α (TNFα) in cultured USMCs. IL-1β treatment reversed H2 S inhibition of CAPs. Knockdown of CSE and CBS prevented H2 S suppression of inflammation. H2 S modulation of inflammation is through KATP channels and phosphoinositide 3-kinase (PI3K) and extracellular signal-regulated kinase (ERK) signaling pathways. H2 S activation of PI3K and ERK signaling is dependent on KATP channels. Our data suggest that H2 S suppresses the expression of CAPs via inhibition of inflammation in myometrium. Endogenous H2 S is one of the key factors in maintenance of uterine quiescence during pregnancy.